1995
DOI: 10.1177/0011000095231002
|View full text |Cite
|
Sign up to set email alerts
|

Internalized Culture, Culturocentrism, and Transcendence

Abstract: Internalized culture is introduced as a psychological, rather than anthropological, construct most useful to counselors. It addresses explicitly both between-group and within-group variations resulting from individual differences in enculturation, and helps to sensitize counselors against overgeneralization and stereotyping. An explication of the construct leads to the problem of defining cultural boundaries. Serious difficulties in definition arise especially when three classes of phenomena are encountered: c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
69
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 19 publications
0
69
0
Order By: Relevance
“…Most anthropologists also claim that there are four basic components of a culture: (1) it is socially transmitted through enculturation; (2) knowledge (people share enough knowledge that they can behave in ways that are acceptable and meaningful to others, so that they do not constantly misunderstand one another); (3) there are shared behavioral regularities or patterns; and (4) there are shared collective experiences of a specific group . Ho (1995) also discussed a definition of culture from an anthropological perspective. He indicated that culture can be conceptualized externally or internally.…”
Section: Defining Culturementioning
confidence: 99%
“…Most anthropologists also claim that there are four basic components of a culture: (1) it is socially transmitted through enculturation; (2) knowledge (people share enough knowledge that they can behave in ways that are acceptable and meaningful to others, so that they do not constantly misunderstand one another); (3) there are shared behavioral regularities or patterns; and (4) there are shared collective experiences of a specific group . Ho (1995) also discussed a definition of culture from an anthropological perspective. He indicated that culture can be conceptualized externally or internally.…”
Section: Defining Culturementioning
confidence: 99%
“…people cany their own version of that culture making individuals unique in their sense of cuiturai identity. As was ernphasized by Ho (1995). it is the intemaiized culture that is rnost significant in understanding diverse indi~lduals.…”
Section: The Etic Positionmentioning
confidence: 99%
“…assimilation, and accommodation can inform this part of supervisors' work. This literature suggests that each supervisory experience may be considered a cross-cultural experience: each person brings to supervision unique life experiences bound in culture and each person integrates knowledge about the professional culture also in a unique way (Ho, 1995). First, supervisees observe professional counselors to vicariously learn acceptable cultural attitudes or stances (e.g., ethics).…”
Section: Acculturationmentioning
confidence: 99%